High neutrophil-lymphocyte ratio upon admission is associated with better response in psychotic depression. (November 2021) - Llorca-Bofí, Vicent; Palacios-Garrán, Roberto; Rey Routo, Diana; Buil-Reiné, Esther; Adrados-Pérez, Marina; Gich, Ignasi; Bioque, Miquel; Mur, Maria
Abstract: Recent evidence relates the inflammatory system to the aetiology and evolution of mood disorders. The Neutrophil-Lymphocyte Ratio (NLR) is an affordable and reproducible biomarker of inflammation. The aim of the study is to retrospectively evaluate the association between NLR and response to treatment in 50 patients aged over 50 with a diagnosis of Psychotic Depression (PD) who were admitted to an acute psychiatric unit between 2010 and 2018. They were stratified according to sex and treatment received: antidepressants, antipsychotics and electroconvulsive therapy (ECT). The NLR was collected on admission and the clinical response was quantified by the Global Assessment of Functioning (GAF) scale. In the simple linear regression, high NLR upon admission was associated with better clinical response during hospitalization as measured by GAF. When stratifying the patients, this association was maintained in women, in patients who received antidepressant treatment with tricyclics and SNRIs, antipsychotic treatment with olanzapine/quetiapine and those who did not receive ECT. NLR is an accessible biomarker in clinical practice, and in PD patients it could guide the therapeutic strategy and be a predictor of response.